What is effective, may be effective, and is not effective for improvement of biochemical markers on muscle damage and inflammation, and muscle recovery? A Systematic Review of PubMed's Database - Renato Carvalho Vilella; Camila Carvalho Vilella (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2020)
Introduction: The Homo sapiens has one of the most amazing characteristic, adaptability. And when adaptability comes to mind, exercising is just by side. Exercising brings many benefits for our body and it is the greater stimulus to trigger musculoskeletal adaptation, starting at mitochondrial level (i.e. biogenesis) to muscular level (i.e. hypertrophy). Mainly when the exercise is of high performance or strenuous, the athlete need a time to recover from fatigue, muscular damage, over-increase of muscular inflammation series of muscle and to prevent overtraining syndrome. Following the concept of "Evidence Based Practice" that is use the best available evidence in clinical decisions, what should be the methods that really have efficacy to prevent or reduce muscle damage, muscle biochemical markers of inflammation and recover? The aim of this article is to search in the PubMed database about what can help our patients/athletes to recover faster, to avoid or to reduce muscle damage and inflammation.  Methods: A search in the PubMed database with the keywords Muscle Skeletal, Inflammation, and Exercise; the keywords had none language translation but results in any language were accepted. Only clinical trials were searched.  Results: 272 articles, 174 excluded (by exclusion criteria). The 98 selected articles were divided into subtopics to discuss their efficacy.  Conclusion: This article evidences the most effective treatments or prevention techniques for improvement of muscle damage, inflammation biochemical markers and muscle recovery.  In our knowledge it is the first in PubMed database that assemble diverse health care subjects, and it may serve as an easy guideline for clinical decision making.